Role of CNNM4 in the progression of cholangiocarcinoma: implications for ferroptosis and therapeutic potential - Mercado-Gómez, Maria; Goikoetxea-Usandizaga, Naroa; Giné, Alvaro Eguileor; Merlos Rodrigo, Miguel A; Afonso, Marta Bento; Azkargorta, Mikel; Zapata-Pavas, Leidy Estefanía; Rejano-Gordillo, Claudia M; Romero, Marta R; Mendizabal, Isabel; Rodrigues, Pedro M; Wu, Hanghang; et al. (Gut, 2025)
BACKGROUND AND OBJECTIVE: Cholangiocarcinoma (CCA) is a heterogeneous neoplasm of the biliary epithelium that easily infiltrates, metastasises and recurs. Magnesium disbalance is a hallmark of CCA, with the magnesium transporter cyclin M4 (CNNM4) being a key driver of various hepatic diseases. This study aims to unravel the role of CNNM4 in the initiation and progression of CCA. DESIGN: CNNM4 protein and gene expression were assessed in vitro, in vivo and in patients with CCA. Silencing of CNNM4 was effectively achieved by using small interfering RNA (siRNA) or short hairpin RNA in CCA cell lines and GalNAc-conjugated siRNA in a transposon-based CCA mice model. The impact of CNNM4 on tumour cell proliferation, migration and invasion to the lungs was evaluated using the chicken chorioallantoic membrane model. Proteomic analysis was employed to elucidate the underlying molecular mechanisms. RESULTS: CNNM4 was upregulated in CCA samples from humans, mice and cell lines. Functional studies demonstrated that CNNM4 deficiency attenuates cell growth, chemoresistance, migration, invasion, cancer stem cell properties and Warburg effect in vitro and in vivo. Proteomic analysis identified nuclear protein 1 as an upstream regulator of CNNM4-induced ferroptosis in CCA, ultimately leading to cell death. The iron chelator deferiprone could reverse the decreased proliferation induced by CNNM4 silencing, while inhibition of the heme oxygenase-1 by zinc protoporphyrin IX affected only the growth of cells with no targeted CNNM4 inhibition, highlighting the specificity of ferroptosis in CNNM4-associated effects. CONCLUSION: This study reveals that increased CNNM4 expression drives CCA progression and malignancy and that its inhibition may be an effective therapeutic strategy to limit proliferation and metastasis in patients with CCA.
Keywords: REACTIVE OXYGEN SPECIES; CHOLANGIOCARCINOMA; IRON METABOLISM; GENE THERAPY